Molecular characterization of the Haemonchus contortus phosphoinositide-dependent protein kinase-1 gene (Hc-pdk-1). Issue 1 (December 2016) - Li, Fa-Cai; Gasser, Robin; Lok, James; Korhonen, Pasi; He, Li; Di, Wen-Da; Yin, Fang-Yuan; Zhou, Rui; Zhou, Yan-Qin; Zhao, Jun-Long; Hu, Min
Abstract Background Phosphoinositide-dependent protein kinase-1 (PDK-1), which functions downstream of phosphoinositide 3-kinase (AGE-1) and activates protein kinases of the AGC family, plays critical roles in regulating biology processes, such as metabolism, growth, development and survival. In the free-living nematodeCaenorhabditis elegans, PDK-1 is a key component of the insulin-like signalling pathway, regulating the entry into and exit from dauer (arrested development). Although it is proposed that similar molecular mechanisms control the transition from the free-living to the parasitic stages of nematodes, nothing is known about PDK-1 inHaemonchus contortus, a socioeconomically important gastric nematode of ruminants. Methods Here, we isolated and characterized thepdk-1 gene (Hc-pdk-1 ) and its inferred product (Hc -PDK-1) fromH. contortus . Using in vitro and in vivo methods, we then studied the transcriptional profiles ofHc-pdk-1 and anatomical gene expression patterns ofHc -PDK-1 in different developmental stages ofC. elegans . Results In silico analysis ofHc -PDK-1 displayed conserved functional domains, such as protein kinase and pleckstrin homology (PH) domains and two predicted phosphorylation sites (Thr226/Tyr229), which are crucial for the phosphorylation of downstream signalling. TheHc-pdk-1 gene is transcribed in all of the main developmental stages ofH. contortus, with its highest transcription in the infective third-stage larvae (iL3) compared with other stages. Transgene constructs, in which respective promoters were fused to the coding sequence for green fluorescent protein (GFP), were used to transformC. elegans, and to localize and compare the expression ofHc-pdk-1 andCe-pdk-1 . The expression of GFP under the control of theHc-pdk-1 promoter was localized to the intestine, and head and tail neurons, contrasting somewhat the profile for theC. elegans ortholog, which is expressed in pharynx, intestine and head and tail neurons. Conclusions This is the first characterization ofpdk-1/ PDK-1 from a trichostrongyloid nematode. Taken together, the findings from this study provide a first glimpse of the involvement ofHc-pdk-1 in the insulin-like signalling pathway inH. contortus .